Physical training does not increase allergic inflammation in asthmatic children - Moreira, A (2008)
The effects of a 3-month physical training programme on airway inflammation and clinical outcomes were studied in school-aged children with asthma. Subjects with persistent allergic asthma (aged 12.7 +/- 3.4 yrs; n=34) were randomly allocated into training and control groups. Exercise consisted of twice-weekly 50-min sessions for 12 weeks. Inflammation was assessed by levels of exhaled nitric oxide, blood eosinophils, eosinophil cationic protein, C-reactive protein, and total and mite-specific immunoglobulin (Ig)E. Lung volumes and bronchial responsiveness to methacholine were determined. The Paediatric Asthma Quality of Life Questionnaire and Paediatric Asthma Caregiver's Quality of Life Questionnaire were used to evaluate activity restrictions, symptoms and emotional stress. The efficacy of the training was assessed by accelerometry. Following the programme, the exercise group spent twice as much time as the controls undertaking moderate-to-vigorous activities. No differences in changes were seen between groups for asthma outcomes. However, total IgE decreased more in the exercise group, as did mite-specific IgE. Training did not increase inflammation in children with persistent asthma, and may have decreased both total and allergen-specific immunoglobulin E levels. It is concluded that there is no reason to discourage asthmatic children with controlled disease to exercise.